″STEM-education of teachers in the countries of the Eastern world and Australia - Valko, N. (Problems of Engineer-Pedagogical Education, 2019)
There are a number of Eastern states, in which there is a significant economic growth and the strengthening of the position of world leaders in technology. According to the results of the international assessment of PISA students, these countries also lead the ranking of educational system ratings. Therefore, the education systems of such states are of interest for research. A critical study of existing solutions for the implementation and popularization of STEM-education can be useful for building our own STEM-education system. It will also offer an opportunity to identify various options for improving the competitiveness of our state. The article provides an overview of the existing educational research in China, Japan, Taiwan, Singapore, and Australia. An overview of the existing regulatory framework and the system of teacher education in these countries has also been made. Although each country defines in its own way a set of STEM-objects and their combinations, in most cases mathematics, science (physics, biology, chemistry) and ICT (digital technologies) take the basis. Emphasis is placed on the system of teacher education (graduate and postgraduate) in mathematical and natural disciplines. There are also examples of initiatives launched by non-state institutions involved in teacher development.